Walking, cycling, and public transport for commuting and non-commuting travels across 5 European urban regions: Modal choice correlates and motivations. (October 2021) - Charreire, H.; Roda, C.; Feuillet, T.; Piombini, A.; Bardos, H.; Rutter, H.; Compernolle, S.; Mackenbach, J.D.; Lakerveld, J.; Oppert, J.M.
Abstract: The objective of this study was to explore individual and contextual-level characteristics associated with active (walking and cycling) and public transport as main travel modes for both non-commuting and commuting purposes, in residents of five European urban regions. We also described participant-reported motivations for modal choice for each journey purpose. The study used multilevel models to investigate cross-sectional associations of individual (i.e. age, gender, educational level) and contextual (defined by a combination of residential neighbourhood characteristics in typologies) characteristics with the choice of active and public transport as outcome. Based on an online survey of 6037 residents of Ghent and suburbs (Belgium), Paris and inner suburbs (France), Budapest and suburbs (Hungary), the Randstad (including the cities of Amsterdam, Rotterdam, The Hague and Utrecht in the Netherlands) and Greater London (United Kingdom), we observed associations with both individual and contextual characteristics. Results of the multilevel modelling show that the probability of using active or public transport as main mode varies depending on both individual and contextual characteristics. At individual level, relations with gender, age, education, weight status and having at least one child varied according to main transport mode and/or purpose. For example, overweight participants reported lower level of cycling for commuting and non-commuting travels than normal-weight participants. In the context of non-commuting travels, participants with one or more child reported less public transport use and more walking (vs participants without children). Among contextual-level variables, urban characteristics of the residential neighbourhood defined by four clusters (according to food environment, recreational facilities and active mobility opportunities) were associated with public transport and walking but not with cycling. For active transport the most important reasons were "I like to travel (on foot or by bike)" and "I want to be physically active" for both travel purposes. "Public transport facilities nearby" was indicated as the most important reason for public transport (for both trip purposes) – the second was "Journey time". Our findings highlight the importance of exploring a combination of multiple correlates at individual and contextual level according to journey purposes and suggest that the role of health-related individual characteristics such as weight status need further exploration. Highlights: Multilevel approach was used to assess individual/contextual correlates of active and public transport in European regions. Both individual and contextual characteristics were identified as correlates. The level of association differed according to trip purposes (commuting vs non-commuting). For both commuting and non-commuting travels, similar main motivations were observed.